2017
DOI: 10.15406/mojt.2017.03.00059
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and Ischemic Stroke: A Brief Review

Abstract: Ischemic stroke is one of the leading causes of morbidity and mortality worldwide. Females are protected against stroke before the onset of menopause. Menopause results in increased incidence of stroke when compared to men. The mechanisms of these differences remain to be elucidated. Considering that there is a postmenopausal phenomenon and females in general, are living longer sex hormone-dependent mechanisms have been postulated to be the primary factors responsible for the premenopausal protection from stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Men and women display profound divergence in the onset, progression, and outcomes of CVD ( 16 ). Young women are protected from CVD throughout adulthood but are at higher risk than men after menopause ( 30 , 62 , 66 ). Indeed, the changes in sex hormones with age in women are essential factors contributing to the differences in cerebral vascular protection in women; however, hormone replacement therapy does not reduce CVD risk in postmenopausal women ( 69 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Men and women display profound divergence in the onset, progression, and outcomes of CVD ( 16 ). Young women are protected from CVD throughout adulthood but are at higher risk than men after menopause ( 30 , 62 , 66 ). Indeed, the changes in sex hormones with age in women are essential factors contributing to the differences in cerebral vascular protection in women; however, hormone replacement therapy does not reduce CVD risk in postmenopausal women ( 69 , 79 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have clearly indicated that there are sex differences in the incidence, prevalence, and outcomes of cerebrovascular disease (CVD), including stroke and dementia. Young women are protected from CVD through adulthood but are at higher risk after the onset of menopause than men ( 30 , 62 , 66 ). Hormone replacement therapy does not reduce CVD risk in postmenopausal women in clinical trials ( 69 , 79 ), suggesting that changes in the levels in sex hormones are not the sole contributing factor to the sex differences in cerebral vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Stroke can occur at any age; however, almost one third occurs below the age of 65 years (Roger et al, 2012). Women are at higher risk for stroke after menopause because of the lack of protective sex hormone (Shekhar et al, 2017b; Sudlow and Warlow, 1997). African Americans have nearly twice the incidence of stroke and a higher rate of mortality as well (Benjamin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gender differences are important risk factors for stroke for multiple reasons, as well as in other chronic diseases. Numerous studies have found that reproductive factors, including hormone replacement therapy use, oral contraceptive use, menopause, and pregnancy, also increase the risk of stroke (3537). Specific risk factors include excess androgen secretion and decreased estrogen during the menopause transition period, as well as abdominal obesity and levels of triglycerides, total cholesterol, low density lipoprotein cholesterol, and fasting blood glucose (38,39).…”
Section: Discussionmentioning
confidence: 99%